PANDANGAN ULAMA TERHADAP KONTRAK HIBRID DAN PELAKSANAANNYA DALAM PRODUK PEMBIAYAAN PERUMAHAN AFFIN HOME INVEST-I(SCHOLARS' VIEW ON HYBRID CONTRACT AND ITS IMPLEMENTATION IN HOUSING FINANCING PRODUCT HOME INVEST Affin-I) (UMRAN - Journal of Islamic and Civilizational Studies, 2016)
Hybrid contract is a contract that combines various contract principles in a product or an activity. There are various Islamic scholars’views on permissibility of practicing the hybrid contracts. The concept of combination of various contracts are applied in Islamic funding institutions in Malaysia through the principle of Musharakah Mutanaqisah (Diminishing Partnership). The Affin Home Invest-i practices Musharakah Mutanaqisah. The objective of this research is to identify the Islamic scholars’ views on hybrid contracts and study on its enforcement in housing finance based on the prinsiple of Musharakah Mutanaqisah in the Affin Home Invest-i at Affin Islamic Bank Berhad. This is a qualitative research with content analysis approach and semi-structure interviews. Results of this research indicates that arguments of the Islamic scholars who permit the combination contract is in high demand and consistent with current needs. This research also found that Affin Islamic Bank Berhad applies the housing finance based on the principle of Musharakah Mutanaqisah by combining the contract of shirkah (partnership), ijarah (renting), and purchase.
Keywords: Hybrid contracrt; Musharakah Mutanaqisah (Diminishing Partnership); Affin Home Invest-i